IMPLEMENTATION OF ACCURATE ONLINE FEATURES TO ENHANCE THE COMPETENCE OF ECONOMICS TEACHERS IN KUDUS SENIOR HIGH SCHOOLS - Budiman, Nita Andriyani; Whetyningtyas, Aprilia (International Journal of Engagement and Empowerment (IJE2), 2025)
This community service activity aimed to enhance the competence of economics teachers who are members of the economics subject teachers’ forum of senior high schools in Kudus Regency through the implementation of Accurate Online features, particularly the fixed assets, cash/bank, and general journal modules. The background of this program lies in the limited understanding of teachers regarding modern accounting software and the insufficient integration of technology in accounting instruction, which has so far relied more on theoretical explanations and traditional practices without utilizing web-based applications. The activity was conducted in August 2025 through four stages: preparation, training and mentoring in the use of Accurate Online, resolution of technical issues encountered by teachers, and evaluation of implementation. The results indicated a significant improvement in teachers’ ability to operate Accurate Online, the achievement of Certified Accurate Professional certification by participants, and an increase in technological accounting knowledge applicable in the learning process. Mastery of Accurate Online features is expected to support teachers in delivering accounting instruction that is more modern, practical, and aligned with industry needs.